Potassium Ion Channel Gene OsAKT1 Affects Iron Translocation in Rice Plants Exposed to Iron Toxicity - Wu, Lin-Bo; Holtkamp, Felix; Wairich, Andriele; Frei, Michael (Frontiers in Plant Science, 2019)
Iron toxicity is one of the most widely-spread mineral disorders in anaerobic soils, but the tolerance mechanisms in plants are poorly understood. Here we characterize the involvement of a rice potassium ion channel gene, OsAKT1, in Fe toxic conditions. Two knock-down lines of OsAKT1 together with azygous lines were investigated. Mutant lines did not differ from azygous lines regarding plant growth, gas exchange rate or chlorophyll fluorescence in control conditions. However, loss-of-function of OsAKT1 increased the sensitivity to excess Fe regarding leaf bronzing symptoms, reactive oxygen species generation, leaf spectral reflectance indices, and chlorophyll fluorescence. Fe toxicity leads to largely reduced uptake of other nutrients into shoots, which illustrates the complexity of Fe stress related to multiple mineral disorders. Less potassium uptake in the mutants compared to azygous lines co-occurred with higher amounts of Fe accumulated in the shoot tissues but not in the roots. These results were consistent with a higher level of Fe loaded into the xylem sap of mutants compared to azygous lines in the early phase of Fe toxicity. In conclusion, OsAKT1 is crucial for the tolerance of rice against Fe toxicity as K homeostasis affects Fe translocation from root to shoot.